Prace Paula Otleta a World Wide Web - Sebastian D Kotuła (Biblioteka)
Paul Otlet’s visualizations of data integration seem to have some distinct parallels with the hypertext used in the World Wide Web. Researchers representing different disciplines (e.g., media specialists, sociologists, IT specialists and librarians) all indicate essential similarities between the attempts at the information and search system conceived by the Belgian author and visionary and that of the WWW. Accordingly, the article aims at finding an answer to the question whether Otlet’s visualizations are convergent to a certain degree with the WWW and whether the authors of the Web modeled their work on the Otlet’s achievements?